The central renin-angiotensin system and sympathetic nerve activity in chronic heart failure - Zucker, Irving H; Xiao, Liang; Haack, Karla K V (Clinical science (1979), 2014)
CHF (chronic heart failure) is a multifactorial disease process that is characterized by overactivation of the RAAS (renin-angiotensin-aldosterone system) and the sympathetic nervous system. Both of these systems are chronically activated in CHF. The RAAS consists of an excitatory arm involving AngII (angiotensin II), ACE (angiotensin-converting enzyme) and the AT1R (AngII type 1 receptor). The RAAS also consists of a protective arm consisting of Ang-(1-7) [angiotensin-(1-7)], the AT2R (AngII type 2 receptor), ACE2 and the Mas receptor. Sympatho-excitation in CHF is driven, in large part, by an imbalance of these two arms, with an increase in the AngII/AT1R/ACE arm and a decrease in the AT2R/ACE2 arm. This imbalance is manifested in cardiovascular-control regions of the brain such as the rostral ventrolateral medulla and paraventricular nucleus in the hypothalamus. The present review focuses on the current literature that describes the components of these two arms of the RAAS and their imbalance in the CHF state. Moreover, the present review provides additional evidence for the relevance of ACE2 and Ang-(1-7) as key players in the regulation of central sympathetic outflow in CHF. Finally, we also examine the effects of exercise training as a therapeutic strategy and the molecular mechanisms at play in CHF, in part, because of the ability of exercise training to restore the balance of the RAAS axis and sympathetic outflow.